Conservation of a mid-19th Century Pretiosa Mitre From New Norcia, Western Australia. Issue 2 (2nd July 2016) - MacLeod, Ian D; Rinske Car, And
Abstract : Conservation treatment and associated scientific analysis of a significant pretiosa (Latin, precious) mitre from the Benedictine Monastery at New Norcia, Western Australia is presented. Analysis of the pH and surface chloride readings showed that increased acidity contributed to the deterioration of the silk fibres, which could be directly related to the levels of retained sweat indicated by the measured chloride ion activity. Migration of acidity from the external silk fabric into the oiled cardboard internal stiffeners necessitated the insertion of replica pieces into the subsequently disassembled mitre. Prior to this work, the corroded gilded silver alloy decorative elements on the disassembled mitre were conserved in situ through reductive consolidation in a 0.1 wt.% sodium dithionite solution at neutral pH. Considerable couching was conducted to stabilise the metalwork and the damaged silk panels on both faces of the mitre, owing to extensive wear from repeated and extended use. Extensive biological degradation of the original silk lining had rendered the original materials with insufficient structural strength to undergo conservation treatment, ultimately requiring replacement with a matching modern silk. All original materials were kept as part of the research collection held by the New Norcia community to allow for future possible DNA analyses.